AORTIC VALVULAR STENOSIS IN ELDERLY POPULATION - Antova, Emilija; Hristova Dimceva, Anita; Stojanoska Bojadzieva, Biljana; Trpkovska, Biljana; Zafirova, Biljana; Lazarova Trajkovska, Emilija (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Aortic valve stenosis (AS) is the most common degenerative valvular disease with an increasing prevalence as a result of prolonged life expectancy. The hemodynamic disturbances that occur in the heart depend on the degree of narrowing of the aortic orifice. AS often remains undiagnosed due to its prolonged asymptomatic period. By the time significant symptoms appear, the disease is usually in an advanced stage, leading to a rapid and steep decline in survival. Echocardiography is the most important diagnostic method, used to analyze the cusps, evaluate the degree of valve calcification, and assess the severity of AS(mild, moderate, or severe) as well as its consequences. A decrease in global longitudinal myocardial strain(GLS) below -16% signifies worsening and predicts future adverse events. Computed tomography (CT) is frequently necessary to determine  calcium score of the aortic valve. Cardiac magnetic resonance imaging (MRI) is valuable for detecting and quantifying myocardial fibrosis.  Patients with severe AS and symptoms should be promptly referred for either an interventional percutaneous procedure, such as transcatheter aortic valve implantation (TAVI) , or surgical aortic valve replacement (SAVR) , when the valve is replaced with either a biological or mechanical prosthesis. The study findings highlight the evolving role of TAVI as a comparable or superior alternative to surgical AVR, particularly in high- and intermediate-risk patients , and suggest similar efficacy in low-risk patients with procedural advantages for TAVI.  Medical management focuses on addressing all cardiovascular risk factors. If an intervention or surgery is not feasible, patients remain on palliative care. Palliative care plays a crucial role in the management of patients with AS or other valvular heart diseases, particularly when the surgery or interventional procedures are not performed on time. Keywords: aortic valve stenosis, TAVI, surgical aortic valve replacement.